ข้อถกเถียงว่าด้วยอำนาจของศาลรัฐธรรมนูญไทยในการยุบพรรคการเมือง พ.ศ.2550 - แพรวา วุฒิการณ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This study entitled, “Debates on Jurisdiction of the Constitutional Court of the Kingdom of Thailand in Case of Political Party Dissolution B.E. 2550”, aimed at analyzing debates regarding the legal status of Constitutional Court in case of the dissolution of a political party code 3-5/2550 and analyzing the constitutional court decision ruling toward the institution of Thai political parties. Importance of this study began with the power of trial of constitutional court and a ruling of the case number 3-5/2550 of constitutional tribunal 2549 B.E., which was appointed by Council For Democratic Reform (Under Constitutional Monarchy) after the announcement using the constitution of the Kingdom of Thailand (Interim) B.E. 2549,section 35, enacted as follows. “Any matters prescribed by law that is under the authority of the constitutioal court or problems regarding whether any law is or is not in contravention of the constitute shall be considered as under the purview of the constitutional tribunal, which consists of the President of the Supreme Court of Justice as President, the President of the Supreme Administrative Court as Vice President, five judges of the Supreme Court of Justice holding a position not lower than Judge of the Supreme Court of Justice and elected at a general meeting of the Supreme Court by secret ballot as constitutional tribunal and two judges of the Supreme Administrative Court elected at a general meeting of the Supreme administrative Court by secret ballots as members. Therefore, all of constitutional tribunal is legal authorities. Any case or other matter still pending under the purview of the Constitutional Court prior to 19 September B.E. 2549 shall be transferred to the authority and responsibility of the constitutional tribunal.” Therefore, the origin of constitutional tribunal from the constitution of the Kingdom of Thailand (Interim) B.E. 2549, is a part of the judicial power that can affect to the legislative power and executive power in practice. Results from the study showed that legal status of constitutional tribunal and judicial power of the constitutional court were certified by the constitution of the Kingdom of Thailand (Interim) B.E. 2549, section 35 as mentioned. From the act identified that cases pending in constitutional court will be transferred to be under the power of consstitutional tribunal. Constitutional tribunal has a power to consider case number 3-5/2550 without violating to the legal state. However, it affected the seperation of powers because the constitutional court judged that the political parties had to be dissoluted, it caused political changes in the parliamentary system, especially to the imbalance among legislative, executive and judicial power, along with Thai political institution. Therefore, the dissolution of political parties, especially parties that were elected from people ruined chances of Thai political parties to develop to be strong institutions in Thai political system. Following were suggestions from the research study. 1. There should be organizations examining the use of judicial power of the Constitutional Court. 2. There should be a clear procedure for consideration on the Constitutional Court in order to be a norm for further court decision ruling. 3. Constitutional tribunal in terms of politics should be increased for more fair trial.